Pro ODP .NET for Oracle database 11g - Zehoo, Edmund (Expert's voice in Oracle., 2010)
"This book is a comprehensive and easy-to-understand guide for using the Oracle Data Provider (ODP) version 11g on the .NET Framework"--Resource description page